Effect of integrated nutrient management on productivity, nutrient uptake and economics of rainfed pigeonpea (Cajanus cajan) and blackgram (Vigna mungo) intercropping system - KUMAWAT, NARENDRA; SINGH, RAJENDRA PRASAD; KUMAR, RAKESH; YADAV, TEJ PRAKESH; OM, HARI (The Indian Journal of Agricultural Sciences, 2015)
Field experiments were carried out during kharif season of 2008-09 and 2009-10 to study the effect of integrated nutrition on productivity, nutrient uptake and economics of rainfed pigeonpea [Cajanus cajan (L.) Millsp.] and blackgram [Vigna mungo (L.) Hepper] intercropping system. Pooled data shows that intercropping systems did not influence significantly on the grain, stover, biological yield and harvest index of pigeonpea and blackgram. Total uptake of N, P, K, S and Zn by pigeonpea were highest recorded with the sole pigeonpea (S1) which was comparable to normal intercropping system (S2) and significantly superior over paired intercropping system (S3). Further, pooled data revealed that normal intercropping system (S2) gave maximum values of gross return (Rupees 120 050), net return (Rupees 99 396), B:C ratio (4.8), pigeonpea equivalent yield (21.75 q/ha), land equivalent ratio (1.70), production efficiency (7.98 kg/ha/day) and economic efficiency (364.83 Rupees/ha/day) which was at par with paired intercropping system (S3) and significantly superior to sole planting of pigeonpea (S1). Application of 100% recommended dose of fertilizers + 50% recommended dose of nitrogen (through vermicompost) + 5 kg Zn/ha gave significantly higher grain yield (21.05 and 5.23 q/ha), stover yield (82.19 and 14.47 q/ha), biological yield (103.24 and 18.85 q/ha) and harvest index (20.23 and 26.40%) of pigeonpea and blackgram, respectively. This treatment (F7) also gave the higher total uptake of N, P, K, S and Zn by pigeonpea and blackgram. Similarly, application of 100% RDF + 50% RDN + 5 kg Zn/ha (F7) recorded highest gross return (Rupees 130 735), net return (Rupees 109 277), B:C ratio (5.11), PEY (24.24 q/ha), LER (1.57), production efficiency (8.9 kg/ha/day) and economic efficiency (401.07 Rupees /ha/day) which was at par with 50% RDF + 100% RDN + 5 kg Zn/ha (F8) and significantly superior to rest of the treatments.